2019
DOI: 10.1111/aos.14207
|View full text |Cite
|
Sign up to set email alerts
|

Primary congenital glaucoma in Denmark, 1977–2016

Abstract: Purpose To perform an epidemiological survey of all patients in Denmark diagnosed with primary congenital glaucoma (PCG) from 1977 to 2016. Methods A retrospective, nationwide study based on a review of medical files of all children with PCG born in Denmark from 1977 to 2016. PCG was defined as glaucoma due to isolated angle dysgenesis affecting children from birth and including late onset/late recognized PCG, excluding glaucoma associated with other congenital abnormalities. Incidence and risk factors of PCG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
(86 reference statements)
0
18
1
4
Order By: Relevance
“…Others have found that more severely affected children have an increased risk of failure (Al-Hazmi et al 2005) and that boys are at greater risk of failure than girls (Hassanein et al 2018). The prevalence of PCG has been reported to be higher in boys by many studies (McGinnity et al 1987;de Silva et al 2011;Suri et al 2015) including in our population (Pedersen et al 2019). The exact mechanism by which male gender could influence both the risk of PCG and the risk of failure of trabeculotomy is, however, unknown.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Others have found that more severely affected children have an increased risk of failure (Al-Hazmi et al 2005) and that boys are at greater risk of failure than girls (Hassanein et al 2018). The prevalence of PCG has been reported to be higher in boys by many studies (McGinnity et al 1987;de Silva et al 2011;Suri et al 2015) including in our population (Pedersen et al 2019). The exact mechanism by which male gender could influence both the risk of PCG and the risk of failure of trabeculotomy is, however, unknown.…”
Section: Discussionmentioning
confidence: 57%
“…Medical charts were retrieved from the different hospitals in Denmark, reviewed and evaluated to verify the diagnosis of PCG and to retrieve relevant medical information. The study cohort has been described previously in detail (Pedersen et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence widely varies depending on the origin of the cohort and the classification of the type of glaucoma (see childhood glaucoma research network, CGRN [ 1 ]). Previous reports from western countries found incidences of primary congenital glaucoma (PCG) ranging from 1:10,000 to 1:40,000 births [ 2 , 3 ] whereas it is higher in countries where consanguine marriage is more common. Thus, in Saudi Arabia the incidence was reported 1:2500 [ 4 ], and the highest incidence of 1:1250 was found in a cohort of Slovakian Romani people [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PCG is common, with a prevalence of >32% in children who suffer from glaucoma ( 7 ). The overall incidence of PCG in Denmark is 4.8 in 100,000 live births ( 8 ).…”
Section: Introductionmentioning
confidence: 99%